Validity and Practicality of the ‘Perisai Diri’ Digital Comic Based on Siri’ Na Pacce Values for the Prevention of Sexual Harassment among Junior High School Students - Latif, Suciani; Fatimah Azzahra Ayu; Sinring, Abdullah; Harum, Akhmad (ILIN Education Indonesia, 2025)
This study evaluated the validity and practicality of the Perisai Diri digital comic as a preventive medium against sexual harassment among junior high school students. Adapting the Borg and Gall research-and-development model into seven stages, the comic integrates Bandura’s Social Learning Theory, assertiveness training, and the Bugis–Makassar philosophy of Siri’ Na Pacce. Expert validation indicated very high feasibility 90 % from content experts, 96 % from media experts, and 99 % from practitioners. A practicality test with one guidance-and-counseling teacher and ten students yielded very high practicality scores (99 % and 95 %, respectively). The comic’s five stories teach body rights, assertive skills, and reporting pathways, reinforcing both self-efficacy and cultural values. These findings confirm that Perisai Diri is scientifically valid and highly practical for culturally grounded school counseling, providing an effective and replicable medium for adolescent sexual-harassment prevention.